Synergistic modulation of gut microbiota and mindfulness-based interventions in schizophrenia: Integrating neurotransmitter regulation and multimodal therapeutic strategies - Izabela Zajkowska; Patrycja Niczyporuk; Aleksandra Giba; Kamila Iłendo; Wiktor Królikiewicz; Rafał Marecki; Aleksandra Kicman (Quality in Sport)
This review explores an innovative, integrative therapeutic approach that combines probiotics, prebiotics, and mindfulness-based interventions (MBIs) to target the dysregulation of the gut–brain axis in schizophrenia. The rationale for this combined strategy is rooted in the overlapping mechanisms by which both biological and psychosocial interventions influence neurophysiological processes. Probiotics and prebiotics are shown to rebalance the gut microbiota, thereby enhancing the synthesis of key neurotransmitters—such as serotonin, gamma-aminobutyric acid (GABA), and dopamine—and reducing systemic inflammation and oxidative stress. In parallel, MBIs, including Mindfulness-Based Stress Reduction (MBSR) and Mindfulness-Based Cognitive Therapy (MBCT), promote improvements in emotional regulation, cognitive function, and neuroplasticity through the modulation of neurophysiological pathways, notably by attenuating amygdala reactivity and heightening prefrontal cortex engagement.